2021
DOI: 10.3390/app11104340
|View full text |Cite
|
Sign up to set email alerts
|

Field Testing Protocols for Talent Identification and Development in Basketball—A Systematic Review

Abstract: Basketball is one of the most popular team sports in the world. A wide variety of athletic skills can be valuable indicators of a talented player. Testing these skills help trainers and scouts to make the best decisions during both youth and adult player selection of different competitive levels and field positions. However, scientific data regarding the association between field tests results and match statistics is sparse. We conducted a systematic review to logically summarize the physical field tests of at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Results of the current and our previous review [24] indicate that general anamnesis, orthopedic-, anthropometric-, and spiroergometric measurements are needed before the offseason period. Although COD (e.g., Lane Agility Drill) and RCOD (e.g., BBAGIL) testing, strength testing (e.g., handgrip strength test, 1RM bench press), and jump testing (e.g., CMJ, DJ) appear to be the most relevant tests during the pre-season, values of the dribbling deficit and COD decrement might also be worthwhile to measure.…”
Section: Recommendations On Test Selectionmentioning
confidence: 83%
See 3 more Smart Citations
“…Results of the current and our previous review [24] indicate that general anamnesis, orthopedic-, anthropometric-, and spiroergometric measurements are needed before the offseason period. Although COD (e.g., Lane Agility Drill) and RCOD (e.g., BBAGIL) testing, strength testing (e.g., handgrip strength test, 1RM bench press), and jump testing (e.g., CMJ, DJ) appear to be the most relevant tests during the pre-season, values of the dribbling deficit and COD decrement might also be worthwhile to measure.…”
Section: Recommendations On Test Selectionmentioning
confidence: 83%
“…The foremost factor is anthropometry. In our previous review [24], we found that body size affects playing position and playing level as well; therefore, experts and researchers always have to normalize their data with anthropometric measures for valid results. For example, allometric scaling models could successfully explain the influence of body size descriptors on performance, so the prediction for the future performance of the player could be more realistic [47].…”
Section: Practical Advice On Test Implementation and Interpretationmentioning
confidence: 99%
See 2 more Smart Citations